2021
DOI: 10.13005/bpj/2181
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants – Derived Natural Products and Phytochemical Extract as Potential Therapies for Coronavirus : Future Perspective

Abstract: On 11th March 2020 , the WHO has declared that the Coronavirus 2 ( SARS-CoV-2) or noval coronavirus ( COVID-19) as Global Pandemic in the whole world . Yet there is no vaccine or any kind of special treatment developed even though all the nations are testing several therapeutic molecules. Different herbs that are traditional are also being used with conventional drugs since the COVID-19 outbreak and are showing promising results in for the treatment of the patients. In this paper, we will review on the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…currently, traditional drug has a lot to offer . ( 20) Some Cases generally respond well to these specifics, indicating a lessening of their symptoms, if not a full relief. Ayurvedic remedies are generally employed in confluence with or after conventional medical treatments because utmost cases begin taking conventional medicinals as soon as they're diagnosed .…”
Section: Part Of Herbal Medicine In Daily Lifementioning
confidence: 97%
See 1 more Smart Citation
“…currently, traditional drug has a lot to offer . ( 20) Some Cases generally respond well to these specifics, indicating a lessening of their symptoms, if not a full relief. Ayurvedic remedies are generally employed in confluence with or after conventional medical treatments because utmost cases begin taking conventional medicinals as soon as they're diagnosed .…”
Section: Part Of Herbal Medicine In Daily Lifementioning
confidence: 97%
“…similar shops, which were formerly believed to be dangerous, have since been set up to contain precious medicinal factors . (20)(21)…”
Section: Part Of Herbal Medicine In Daily Lifementioning
confidence: 99%
“…The antiviral activity of the extracts of medicinal plants and their bioactive compounds have been confirmed by in vitro , in vivo , and in silico assays to inhibit direct entry of the SARS-CoV-2 and ACE2 receptors as well as block the serine protease TMPRRS2. It is also reported that medicinal plants can inhibit papain-like or chymotrypsin-like proteases that are required in the life cycle of SARS-CoV-2 [ 4 , 24 ]. Several plant biometabolites including extracts have been reported previously for in vivo and in vitro anti-coronavirus properties such as lectins, saikosaponins, emodin, quercetin derivatives, lectin, ethanolic, and water extract of the plant parts or whole plant [ 81 ].…”
Section: Main Textmentioning
confidence: 99%
“…Este producto natural tiene efectos antiinflamatorios e inhibidores contra el COVID-19. (Ahmad SR, 2021) Existen reportes de que extractos de Rheum officinale, comúnmente conocida como Ruibarbo y Polygonum multiflorum (nombre común: Solimancillo o Soliman) puede inhibir la unión de ACE-2 con la proteína S en el SAR-COV-1, con valores de IC50 entre 1-10 μg/mL. La emodina, con estructura de antraquinona, es un ingrediente activo en este género y se ha mostrado que bloquea significativamente la proteína S, es por eso que los autores la sugieren como un tratamiento potencial para el COVID-19 (TY, Ho, Wu SL, Chen JC, Li CC, 2007) El bloqueo de entrada del ARN del SAR-COV-2 a la célula hospedadora ha hecho que los estudios se enfoquen a la proteína ACE-2.…”
Section: Revista Conectividad Julio-diciembre 2022unclassified